PENGARUH BUDAYA TULIS MENULIS PENDUDUK MADINAH TERHADAP PERKEMBANGAN PENULISAN HADIS - Yor Hananta (UIN Siber Syekh Nurjati Cirebon, 2020)
The purpose of writing this article is to describe the cultural influence of writing the inhabitants of Medina on the development of Ḥadîth during the hijra of the Prophet. As it is known to the general public that Medina became the center of Islamic civilization that exerted significant influence in advancing Islam to establish a sovereign state. This study is qualitative research, data obtained from library sources, and analysis conducted using descriptive analysis to obtain an overview of the purpose of this study. The results of the study obtained in this article illustrate the extent of the cultural development of the inhabitants of Medina, especially the Arabs, the development of Ḥadîth during hijra, and the relationship between the culture of the writings of the inhabitants of Medina to the development of Ḥadîth. The findings obtained in this article describe the culture of writings of the inhabitants of Medina, the development of Ḥadîth that occurred in this period is in the increasing spread of Ḥadîth in quality and quantity through oral intermediaries. The latest finding is that there is no significant link between the writing culture of the inhabitants of Medina and the development of Ḥadîths that occur in it against the backdrop of the brlakang presented in the results and discussion of the article.Keywords: Ḥadîth Writing; Writing Culture; Medina Islam Tujuan penulisan artikel ini adalah untuk menggambarkan pengaruh budaya tulis menulis Penduduk Madinah terhadap perkembangan hadis pada masa hijrah Nabi. Sebagaimana diketahui khalayak umum bahwa Madinah menjadi pusat peradaban Islam yang memberi pengaruh signifikan dalam memajukan Islam hingga membangun sebuah negara yang berdaulat. Kajian ini merupakan penelitian kualitatif, data yang diperoleh dari sumber kepustakaan, dan analisis yang dilakukan menggunakan analisis deskriptif guna memperoleh gambaran yang menjadi tujuan penelitian ini. Hasil penelitian yang diperoleh dalam artikel ini menggambarkan sejauh mana perkembangan budaya tulis-menulis penduduk Madinah khususnya bangsa Arab, perkembangan hadis pada masa hijrah, dan hubungan antara budaya tulis-menulis penduduk Madinah terhadap perkembangan hadis. Temuan yang diperoleh dalam artikel ini menggambarkan bururknya budaya tulis-menulis penduduk Madinah, perkembangan hadis yang terjadi dalam kurun waktu ini ada pada peningkatan penyebaran hadis dalam kualitas dan kuantitas melalui perantara lisan. Temuan terakhir adalah tidak ditemukannya hubungan yang signifikan antara budaya tulis-menulis penduduk Madinah dengan perkembangan hadis yang terjadi di dalamnya dengan latar brlakang yang disajikan dalam hasil dan pembahasan artikel.Kata Kunci: Penulisan Hadis; Budaya Tulis Menulis; Islam Madinah